Motivasi Kerja dan Profesionalisme Memoderasi Pengaruh Kompleksitas Tugas Pada Kinerja Auditor - Sari, Lina Dwi Kumala; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2017)
Audit quality is determined by the performance of the auditor performing the audit assignment. For that research focus on auditor performance with aim to know whether work motivation and professionalism as moderator of influence of task complexity at auditor performance at Office BPK RI Representative of Bali Province. Determination of the sample using saturated sampling method where data collection is done by using questionnaire. The number of research samples used was 36 respondents. Data analysis technique used is MRA analysis technique. The results of this study indicate that (1) task complexity has a positive effect on auditor performance which means that the higher the task complexity the higher the performance of an auditor; (2) professionalism strengthens the influence of task complexity on auditor performance, (3) task complexity on auditor performance